Features of helium complexes behaviour near the free surface in tungsten - Starchenko, I.V.; Sadanov, E.V. (Вопросы атомной науки и техники, 2019)
The formation of interstitial atoms by lattice tungsten atoms displacement by clusters of implanted helium, which is accompanied with the appearance of helium-vacancy complexes, was found. The stimulating effect of the free surface on the development of the processes of displacement and dissociation of complexes has been revealed. It is shown that this influence is caused by the action of image forces. The depth of the image forces was determined, which was about 2.5 nm.